UTILIZING QUALITATIVE RESEARCH IN RELIGIOUS-BASED CHARITY GOVERNANCE: EXPERIENCE AND VALUE LESSON - Nur Farahiah Azmi; Hazriah Hasan; Mohd Nor Hakimin Bin Yusoff; Siti Rohana Mohamad, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Qualitative research is highly acknowledged for their valuable contribution to various research disciplines, including governance. Therefore, this paper aimed to report real-life researcher experience in conducting an interview with Islamic charity. Findings from this study revealed four main challenges faced by the researchers, such as participant recruitment, language barrier, confidentiality, and time and venue for the interview. Such outcomes offered valuable insight for future researchers regarding possible challenges and their subsequent solutions in conducting interviews in the context of Islamic charity governance research.